2022
DOI: 10.3390/agronomy12030631
|View full text |Cite
|
Sign up to set email alerts
|

Organic Farming Provides a Blueprint to Improve Food Quality, Safety and Security

Abstract: The increasing reliance on non-renewable resources (in particular, mineral nitrogen, phosphorus and potassium fertilizers and synthetic chemical pesticides) to sustain current productivity levels of agriculture are of growing concern, because these inputs have substantial negative environmental impacts and may become too expensive and/or unavailable in the future [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…The growth of the world’s population more than twofold, from 3 billion people in 1960 to 7.7 billion people at present, has entailed a forced increase in agricultural production [ 1 , 2 ]. This has led to increased consumption of mineral fertilizers [ 3 , 4 , 5 ]. The growing demand for mineral fertilizers has required an increase in the production capacity of enterprises producing potash fertilizers [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…The growth of the world’s population more than twofold, from 3 billion people in 1960 to 7.7 billion people at present, has entailed a forced increase in agricultural production [ 1 , 2 ]. This has led to increased consumption of mineral fertilizers [ 3 , 4 , 5 ]. The growing demand for mineral fertilizers has required an increase in the production capacity of enterprises producing potash fertilizers [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, the main driver for consumer demand for organic products, including olive oil and table olives, have been consumer perceptions that organic foods have a higher Agronomy 2022, 12, 1484 2 of 13 nutritional value and result in health benefits [6,19,20]. However, although there is mounting evidence that organic management improves the nutritional composition/quality in a range of crops (including cereals, vegetables and fruit) [6,[21][22][23][24], there is limited information for table olives and olive oil [25][26][27][28][29], except for the well-documented problem of organophosphate (OP) pesticide residues (OPs are used for olive fly control) in conventional olive oil [30,31]. Additionally, most previous studies reported no substantial differences in nutritional quality parameters between organic and conventional olive oil [26][27][28][29], except for a recent study by López-Yerena et al [25], which reported significantly higher concentrations of phenolic compounds in organic compared with conventional extra virgin olive oil of the variety Hojiblanca and one study which reported higher oleic acids in organic production [32].…”
Section: Introductionmentioning
confidence: 99%